GACOR : GERAKAN AKSI CEGAH OLAH RESIKO AIR BERSIH DARI KITA UNTUK KITA (AKE KOROHO TOMA NGONE TE NGONE) - Lestari, Tutik; Amalia, Hestyn; Bada, Wahdi; Sumarto, Sabaria; Diman, Tiara; Aldjokdja, Retno Kartika; Aulia, Rifanda; Sahsun, Darmila; Langasa, Siti AIgina; Daud, Ruslia; Manteto, Tiara; Salim, Nurmai; Minggu, Musdalifa; M, Fitra Tunisyah; Fadilah, Fadilah; Hasan, Risma Hi; Laego, Riyanti (MAJU : Indonesian Journal of Community Empowerment, 2025)
Providing water to meet community needs is a crucial agenda for ensuring basic needs. Despite relatively abundant water availability, communities often struggle to access clean water. The Tosa Village community faces serious water quality issues. The purpose of this activity is to increase public knowledge and awareness, and provide practical solutions for community self-reliance regarding the importance of clean water access. The activity took the form of training and field practice in making simple water filters. Participants included 25 community representatives and PBL II students. Through education, training, and active involvement in making simple water filters from local materials, the community not only gained affordable technical solutions but also raised awareness of the importance of maintaining water quality. This approach strengthens self-reliance, accelerates healthy behavior changes, and directly contributes to the achievement of Sustainable Development Goals (SDG 6). This community-based initiative can serve as an effective model for addressing the clean water crisis in an inclusive and sustainable manner.